2018
DOI: 10.1177/1744806918783931
|View full text |Cite
|
Sign up to set email alerts
|

Plastic change of prefrontal cortex mediates anxiety-like behaviors associated with chronic pain in neuropathic rats

Abstract: Clinical studies show that anxiety and chronic pain are concomitant. The neural basis for the comorbidity is unclear. The prefrontal cortex (PFC) has been recognized as a critical area for affective disorders and chronic pain modulation. In this study, we examined the role of the PFC in the pathogenesis of anxiety associated with chronic pain in a rat model of neuropathic pain with spare nerve injury (SNI). The SNI rats showed apparent anxiety-like behaviors in both open field (OF) test and elevated-plus maze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 112 publications
1
28
0
3
Order By: Relevance
“…Anxiety-like behavior following SNI has been found in both rats and mice. In rats, anxiety-like behavior has been observed in the elevated plus-maze and open field tests at different postoperative times: day 14 [40], day 21 [40,41], day 28 [34,42], days 20-40 [43] and it continues for between 8 weeks [44] and 24 weeks [38]. Interestingly, other studies have failed to observe anxiety-like behavior in the rats subjected to SNI using the same tests over a long observation period ranging from 7 to 19 weeks [27,45].…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety-like behavior following SNI has been found in both rats and mice. In rats, anxiety-like behavior has been observed in the elevated plus-maze and open field tests at different postoperative times: day 14 [40], day 21 [40,41], day 28 [34,42], days 20-40 [43] and it continues for between 8 weeks [44] and 24 weeks [38]. Interestingly, other studies have failed to observe anxiety-like behavior in the rats subjected to SNI using the same tests over a long observation period ranging from 7 to 19 weeks [27,45].…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 99%
“…Intriguingly, Guida et al [33] observed that 30 days-SNI mice showed an overall decreased activity of mPFC pyramidal neurons with a subsequent reduced level of glutamate correlated with pain-related depression-like behavior, cognitive impairments, and obsessive-compulsive-like disorder. Sang et al [44] suggested that the mPFC endures plastic changes after SNI (15 days), as indicated by an elevation of serotonin transporter (SERT) expression, as well as, a greater enhancement of its local field potential (LFP) theta-frequency associated with anxiety-like behavior in avoiding anxiogenic environment. The anxiety-like behaviors of the SNI rats were effectively suppressed by local application of serotonin to the mPFC.…”
Section: Electrophysiological Characterization Of Sni Modelmentioning
confidence: 99%
“…Thus, decreased microglia activation reduced neuropathic pain behavior and the levels of inflammatory mediators, depending on the presence or absence of a depressive phenotype. Other studies have indicated that that anxiety and chronic pain are concomitant, but neural substrates for their comorbidity are unclear [90].…”
Section: Affective Disorders and Neuropathic Painmentioning
confidence: 99%
“…Human studies have shown a positive correlation between DED severity and symptoms of anxiety 7,[60][61][62] . While there have been some reports of increased signs of anxiety in chronic pain models, other reports have not found a significant effect of pain on anxiety measures [63][64][65][66][67][68][69][70] . Using the elevated plus maze, single LGE reduced open arm time only in female mice, whereas double LGE reduced open arm time in both female and male mice.…”
Section: Discussionmentioning
confidence: 92%